Application of electrical method to vertical HDPE film detection in landfill - Wang Kangbo; Chu Yongli; Nai Changxin (E3S Web of Conferences)
According to the structure characteristics and site conditions of vertical HDPE film, the resistivity method is applied to the detection of vertical HDPE film. The double-arranged high-density electrical method was used to collect the data of vertical HDPE film, reverse the distribution of the profile resistivity on the vertical film, and detect the integrity of vertical HDPE film. The test was conducted combined with a landfill in Yancheng City, Jiangsu Province. And through site excavation, the effectiveness of resistivity method in vertical HDPE film detection was verified, and the shortcomings of traditional detection methods were solved. The experimental results show that: resistivity method can effectively, quickly and accurately locate shallow holes. Due to the presence of leachate, low-resistivity anomalies appear near the defects.